Influence of AC waveforms on stress corrosion cracking behaviour of pipeline steel in high pH solution. (2nd January 2016) - Zhu, M.; Ou, G.; Jin, H.; Du, C.; Li, X.; Liu, Z.
Abstract : The effect of various waveforms AC on stress corrosion cracking (SCC) behaviour and mechanism of X80 pipeline steel was investigated in high pH carbonate/bicarbonate solution by polarisation curves and slow strain rate tensile tests. Under various waveforms AC, the passivity of the steel degrades severely, and pitting corrosion easily forms on the electrode surface. With or without AC application, the SCC behaviour and mechanism of the steels in the solution are distinctly different. Without the presence of AC, the cracks propagation are intergranular, and the mechanism is anodic dissolution. AC significantly increases the SCC susceptibility of pipeline steel. The order of the SCC susceptibility of the steel at various waveforms AC is: sine wave < square wave < triangular wave. Under a long term AC interference, the fracture mode is transgranular, and the mechanism of the steel in high pH solution is controlled by anodic dissolution and hydrogen embrittlement.